ANALYSIS OF DECISION SUPPORT CRITERIA TYPE OF HOME INDUSTRY BUSINESS BASED ON ANALYTICAL HIERARCHY PROCESS - Hilyah Magdalena; Hadi Santoso (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: This research was conducted in the Bangka Belitung region specifically observing what criteria could support and hinder the development of home industries. The home industry is a small-scale industry that is generally carried out in the family sphere and is driven by women. Home industries need to receive support from the provincial government to survive and increase the scale of production. To make support for home industries more targeted, this research summarizes several criteria related to the conditions of home industries and the businesses they run. In Bangka Belitung Province there are several types of businesses that are run on a home industry scale. Based on the condition of the home industry which has multiple criteria and multiple alternatives, this research uses the Analytical Hierarchy Process method and Expert Choice software as data processing aids. The results of data processing show that industrial business is the highest alternative with a weight of 24.7% and the highest criterion is strategy at 23.7%. These results indicate that the largest portion of home industry business actors is engaged in the industrial sector and to encourage the progress of the home industry the most important factor is strategy, namely understanding the type of business they are involved in, labor-intensive industries, paying attention to production factors, electricity capacity, and business operations. While the next stage is to design a user interface for a web-based system as a means of collecting home industry data.           Keywords: AHP; collecting home industry data; home industries Abstrak: Penelitian ini dilakukan di wilayah Bangka Belitung secara khusus melihat kriteria apa saja yang dapat mendukung dan menghambat perkembangan industri rumah tangga. Industri rumah tangga merupakan industri kecil yang umumnya dilakukan dalam lingkup keluarga dan digerakkan oleh perempuan. Industri rumah tangga perlu mendapat dukungan dari pemerintah provinsi agar bisa bertahan dan meningkatkan skala produksinya. Agar dukungan industri rumah tangga lebih tepat sasaran, penelitian ini merangkum beberapa kriteria terkait kondisi industri rumah tangga dan usaha yang dijalankannya. Di Provinsi Bangka Belitung terdapat beberapa jenis usaha yang dijalankan dalam skala industri rumah tangga. Berdasarkan kondisi industri rumah tangga yang memiliki banyak kriteria dan banyak alternatif, maka penelitian ini menggunakan metode Analytical Hierarchy Process dan software Expert Choice sebagai alat bantu pengolahan data. Hasil pengolahan data menunjukkan bahwa bisnis industri merupakan alternatif tertinggi dengan bobot 24,7% dan kriteria tertinggi adalah strategi 23,7%. Hasil tersebut menunjukkan bahwa porsi terbesar pelaku usaha industri rumah tangga bergerak di sektor industri dan untuk mendorong kemajuan industri rumah tangga faktor yang paling penting adalah strategi yaitu memahami jenis usaha yang digeluti, industri padat karya, pembayaran, memperhatikan faktor produksi, kapasitas listrik, dan operasional usaha. Sedangkan tahap selanjutnya adalah merancang antarmuka untuk sistem berbasis web sebagai sarana pendataan industri rumahan. Kata kunci: AHP; industri rumahan; pendataan industri rumahan